1993
DOI: 10.1128/aem.59.5.1425-1429.1993
|View full text |Cite
|
Sign up to set email alerts
|

Growth and cholesterol oxidation by Mycobacterium species in Tween 80 medium

Abstract: Mycobacterium strain DP was isolated from marine coastal sediment and tested for its ability to oxidize cholesterol in Tween 80-cholesterol (2.59 mM) medium. Strain DP degraded cholesterol to 4-cholesten-3-one (cholestenone), 4-androsten-3,17-dione (AD), 1,4-androstadien-3,17-dione (ADD), testosterone, and 1-dehydrotestosterone (DHT). Cholesterol disappeared in about 4 days. Cholestenone, AD, testosterone, and DHT accumulations were transient with peak concentrations of 300, 600, 30 to 40, and 21 tLM. ADD prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Some of the microorganisms used to produce cholestenone from cholesterol are Mycobacterium sp. (Smith et al, 1993), R. equi (Ahmed and Johri, 1993), Escherichia (Panchishina, 1992), Nocardia rubra (Osipowicz et al, 1992), A. simplex (Liu et al, 1994a), R. erythropolis (Jadoun and Bar, 1993), R. equi (Myamato and Toyoda, 1994), Agrobacterium sp. M4 (Mahato and Garai, 1997;Yazdi et al, 2000).…”
Section: Biotransformationsmentioning
confidence: 99%
“…Some of the microorganisms used to produce cholestenone from cholesterol are Mycobacterium sp. (Smith et al, 1993), R. equi (Ahmed and Johri, 1993), Escherichia (Panchishina, 1992), Nocardia rubra (Osipowicz et al, 1992), A. simplex (Liu et al, 1994a), R. erythropolis (Jadoun and Bar, 1993), R. equi (Myamato and Toyoda, 1994), Agrobacterium sp. M4 (Mahato and Garai, 1997;Yazdi et al, 2000).…”
Section: Biotransformationsmentioning
confidence: 99%
“…Comparisons were made between root homogenate enrichments and those attempted with inoculants from decaying whale bones and surrounding sediment. Liquid cultures were made with filtered seawater and one of the following substrates: 2.5 mM cholesterol (with 0.1% Tween 20), collagen (0.5% w/ v, 0.1% Tween 20), fatty acids (1 mM) and fish oil (1:1000 v/ v) (Smith et al, 1993;DSMZ, 2004). Agar plates were made with artificial seawater (30 g Instant Ocean l -1 ) with 2% agarose and the following substrate levels: 2.5 mM cholesterol (with 0.1% Tween 20), collagen (0.1% w/v), fatty acids (5 mM) and fish oil (1:1000 v/v).…”
Section: Enrichment Culturesmentioning
confidence: 99%
“…During the course of this work, Dlugovitzky et al (2015) have shown that Mycobacterium smegmatis PTCC 1307 was able to produce TS and other estrogens from tritiated precursors. However, TS has not been detected as a metabolic intermediate when M. smegmatis mc 2 155 is cultured in the presence of phytosterols or cholesterol, neither in the wild-type strain nor in the AD-producing strain (Gal an et al, unpublished), unlike in other mycobacterial species (Wang et al, 1982;Smith et al, 1993;Egorova et al, 2002b). This observation suggests that M. smegmatis mc 2 155 does not contain a functional gene encoding a 17b-HSD or at least, it is not induced in the presence of these compounds.…”
Section: Introductionmentioning
confidence: 99%